The Research Synthesis by Using Meta-Analytic Structural Equation Modeling (MASEM) - Kulprateepunya, Kunthida; Amornchai, Ruangurai (Journal of Health Science of Thailand, 2017)
Meta- Analytic Structural Equation Modeling (MASEM) is an advanced statistics to analyze data that compose complex variables model. MASEM combines 2 methods by assembling metaanalysis and structural equation model. MASEM is considered useful for creating theory by metaanalysis method. Researchers could support or reject theory by examine the overall association of model. Moreover, researchers can examine the relationship across the studies as such MASEM can solve the complex model through the combination of many studies.